2011
DOI: 10.1021/jp111640t
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Driven by Concentration at the Solid–Liquid Interface

Abstract: To tune the structures and properties of self-assembled architectures of organic molecules different building strategies like functional groups; 2À12 substrate; 14À19 temperature; 20À22 chemical nature of solvent (aromatic interaction, 13,23 oddÀeven or parity effect, 24À26 saturated and unsaturated solvent, 27 alkyl chain length 1,2,10 ); properties of solvent (solubility, hydrophilic, and hydrophobic properties, 28 polarity, 29 chirality, viscosity 30 ); and so on have been used. Out of all of these, functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 46 publications
3
27
1
Order By: Relevance
“…Both networks were present at the same time when heptanoic acid was used as a solvent. Hietschold et al 33,36 reported that by tuning the molecule concentration by sonication, TMA selfassembled in flower, filled-flower, and dodeca-rim structures in heptanoic acid, while the chickenwire structure was not observed for these conditions. In contrast to Lackinger et al, 31 both chickenwire and flower structures could be observed in octanoic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both networks were present at the same time when heptanoic acid was used as a solvent. Hietschold et al 33,36 reported that by tuning the molecule concentration by sonication, TMA selfassembled in flower, filled-flower, and dodeca-rim structures in heptanoic acid, while the chickenwire structure was not observed for these conditions. In contrast to Lackinger et al, 31 both chickenwire and flower structures could be observed in octanoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…So far, this structure has never been reported for TMA dissolved in nonanoic acid. 31,33 (highlighted in yellow) and cyclic trimeric (highlighted in blue) hydrogen bonds. The unit cell parameters for the flower structure were found to be a = b = 2.5 nm and θ = 60 • , which match the values reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful control over concentration can aid in selecting a specific structure, especially when two or more polymorphs are possible that differ in packing density or adsorption energy [30][31][32][33][34][35]. One of the first examples of concentration-dependent self-assembly was discovered in the case of alkoxylated DBA derivatives [30].…”
Section: Role Of Concentrationmentioning
confidence: 99%
“…A number of experimental parameters have already been identified that control the appearance of a certain type of polymorph over another. A non-comprehensive list of these parameters includes the type of solvent [23][24][25][26][27][28][29], the concentration of molecules [30][31][32][33][34][35], the type of substrate [36][37][38][39][40][41], the temperature at which the self-assembly takes place [42][43][44][45] and the thermal history of the sample [46]. How these parameters affect the self-assembly of organic building blocks is the subject of this review, with a special focus on the liquid-solid interface.…”
Section: Introductionmentioning
confidence: 99%